Oral Potentially Malignant Disorders: Etiology, Pathogenesis, and Transformation Into Oral Cancer - Kumari, Pratima; Debta, Priyanka; Dixit, Anshuman (Frontiers in Pharmacology, 2022)
Among oral diseases, oral cancer is a critical health issue due to its life-threatening potential. Globocan, in its 2020 report, estimated ~0.37 million new cases of oral cancer, majority of them are coming from Asia. WHO has anticipated a rise in the incidences of oral cancer in the coming decades. Various factors such as genetic, epigenetic, microbial, habitual, and lifestyle are closely associated with oral cancer occurrence and progression. Oral lesions, inherited genetic mutations (dyskeratosis congenita syndrome), and viral infections (HPV) are the early sign of oral cancer. Lesions with dysplastic features have been categorized under oral potentially malignant disorders (OPMDs), such as oral leukoplakia, erythroplakia, oral submucous fibrosis (OSMF), and proliferative verrucous leukoplakia assume to have high risk of malignancy. The incidence and prevalence of OPMDs are recorded high in South-Asian countries. Early detection, prevention, and treatment of OPMDs are needed to prevent its malignant transformation into oral cancer. Many advanced diagnostic techniques are used to predict their progression and to assess the risk of malignant transformation. This communication provides insight into the importance of early detection and prevention of OPMDs.